Application of axiomatic design concepton improving ladder for pepper harvesting - Noraship, M.R (Universiti Malaysia Sarawak, UNIMAS, 2008)
Pepper harvest is a difficult operation and sometime can bring hazard. Ladder is used in this operation to assist farmers to reach the higher portion of pepper tree. It shows ladder is the important devices in the agriculture field. Ladder for pepper harvest was designed to facilitate the farmers in harvesting operation. The application of axiomatic concept is used in this project to facilitate the designing process. Location surveys for this project have been conducted at several farm and orchard at Serian area to identify farmer’s problems regarding the harvesting operation. After problems are identified, the new design of ladder was proposed to fulfill the user needs. Then, from the conceptual phase, the design has through several phases steps by steps to ensure the ladder achieve the best solution and every details assumption is bring into account until the final design is constructs using computer software. The maximum allowable load for the ladder is calculated using solid modeling simulation analysis to estimate the endurance of the material proposed for the ladder and the total rough cost for the proposed ladder is estimated too, to make sure the design is affordable by the users. For the final design, the ladder is providing with platform and wheel together with the unique braking system to ensure it easy and effective for the users.